2019
DOI: 10.1111/jgh.14746
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis on the incidence and prevalence of autoimmune hepatitis in Asian, European, and American population

Abstract: Background and Aim Reported incidence and prevalence rates of autoimmune hepatitis (AIH) have been sparse and heterogeneous. The aim of this meta‐analysis was to estimate the worldwide incidence and prevalence rates of AIH and reveal population difference. Methods Published articles on the epidemiology of AIH in PubMed, Embase, and Cochrane Library were systematically searched from inception to April 28, 2019. Two investigators independently reviewed these literatures and evaluated their quality. A random‐effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 44 publications
1
58
0
1
Order By: Relevance
“…demonstrated that in melanoma patients who were treated with ipilimumab, female sex was significantly associated with a higher risk of severe irAE 9 . Female sex is a risk factor for several autoimmune diseases, including autoimmune hepatitis; 23 thus, sex could influence the incidence of irAE hepatitis. In addition, as in previous reports, 24,25 our study showed that male sex is significantly associated with a high objective response rate (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that in melanoma patients who were treated with ipilimumab, female sex was significantly associated with a higher risk of severe irAE 9 . Female sex is a risk factor for several autoimmune diseases, including autoimmune hepatitis; 23 thus, sex could influence the incidence of irAE hepatitis. In addition, as in previous reports, 24,25 our study showed that male sex is significantly associated with a high objective response rate (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and environmental factors seem to play a crucial role. Despite being a rare liver disease with an estimated prevalence of 2-17 cases per 100'000 in Europe, we observe a notably increase in disease incidence within the last years [2]. In some cases, patients present an overlap to other hepato-biliary diseases such as primary biliary cholangitis (PBC) or primary sclerosing cholangitis (PSC).…”
Section: Introductionmentioning
confidence: 81%
“…However, this disease presents with a strong female predominance and geographic variation [ 1 ]. As summarized in a recent meta-analysis, the AIH has a global annual incidence of 1.37 per 100,000 (1.11 for female and 0.22 for male) and prevalence 17.44 per 100,000 (12.77 for female and 2.91 for male) [ 2 ]. The pooled annual incidence rate in Asian (1.31/100,000) is similar to that in European (1.37/100,000) and American population (1.00/100,000); however, the pooled prevalence rate in Asian (12.99/100,000) is lower than that in European (19.44/100,000) and American population (22.80/100,000) [ 2 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…As summarized in a recent meta-analysis, the AIH has a global annual incidence of 1.37 per 100,000 (1.11 for female and 0.22 for male) and prevalence 17.44 per 100,000 (12.77 for female and 2.91 for male) [ 2 ]. The pooled annual incidence rate in Asian (1.31/100,000) is similar to that in European (1.37/100,000) and American population (1.00/100,000); however, the pooled prevalence rate in Asian (12.99/100,000) is lower than that in European (19.44/100,000) and American population (22.80/100,000) [ 2 ]. One possible explanation for this incidence–prevalence discrepancy would be the late onset or diagnosis and shorter survival of the AIH in Asian population [ 3 , 4 ].…”
Section: Epidemiologymentioning
confidence: 99%